"A frightening experience, especially at our age": Examining the neglect and abuse of older persons in HIV prevention and care programs - Makandwe Nyirenda; Makandwe Nyirenda; Sizakele Sukazi; Cebo Buthelezi; Jill Hanass-Hancock; Jill Hanass-Hancock (Frontiers Media S.A., 2023)
BackgroundAs the global population ages and the HIV pandemic matures, a growing number of older persons aged ≥50 years are becoming increasingly vulnerable to acquiring HIV. Unfortunately, older persons are often neglected and left out of sexual health programs and services. This study explored the experiences of older persons living with and without HIV in accessing prevention and care services and how those experiences translate into the neglect and abuse of older persons. The study also explored older people's perspectives on community responses to HIV in older people.MethodsThis qualitative analysis used data from 37 individuals who participated in focus group discussions conducted in 2017/2018 across two communities in Durban, South Africa. Using an interview guide and thematic content analysis, salient themes regarding attitudes to HIV in older persons and factors of access to HIV prevention and cares services for older persons were analyzed.ResultsThe study participant's mean age was 59.6 years. Major themes emerging from the data included factors impacting HIV prevention and transmission in older people; community responses to HIV contributing to the abuse of older people, and structural drivers of abuse in older people living with HIV (OPLHIV). Knowledge about HIV and how to protect themselves from HIV was limited among participants. Older persons were frightened to acquire HIV at an older age as they feared judgment and discrimination for getting HIV at that age. OPLHIV reported frequently experiencing community stigma and poor staff attitudes and practices at health facilities, such as a triage health delivery system that fueled community stigma. Participants also experienced neglect, verbal and emotional abuse at healthcare facilities.ConclusionAlthough there were no reports of physical and sexual abuse of older persons in this study, this study shows that despite decades of HIV programs in the country, HIV-related stigma, discrimination, and disrespect of older persons remain pervasive in the community and at health facilities. As an increasing number of people age and live longer with HIV, the neglect and outright abuse of older persons need urgent policy and program interventions.